Thermoelectricity Recent Advances, New Perspectives and Applications - Qin, Guangzhao (IntechOpen, 2022)
Next-generation energy sources are crucial for combating the world's energy crisis. One such alternative energy source is thermoelectricity, which is cost-efficient and environmentally friendly. This book presents a comprehensive overview of the progress made in thermoelectrics over the past few years with a focus on charge and heat carrier transport from both theoretical and experimental viewpoints. It also presents new strategies to improve thermoelectricity and discusses device physics and applications to guide the research community.